On the purity of European consciousness in the existential anthropology of early M. Heidegger - Okorokov, V. B (Anthropological Measurements of Philosophical Research, 2022)
Purpose. The purity of consciousness in European culture has practically been turned into an abstraction. Because of this, there are so many discrepancies in understanding its nature. For Heidegger, the question of the purity of human consciousness remains open. Our purpose is to study the purity of European consciousness in the work of M. Heidegger. Theoretical basis. We draw on the deep foundations of existential, phenomenological, hermeneutic, religious-philosophical and postmodern Western and Eastern thought. Originality. While the early Heidegger was thinking under the sign of Dasein, he did not hear the nature of the "pure consciousness" of human. Nevertheless, temporality for him was such a fundamental property that it determined the depth of understanding not only of being, but also of human consciousness itself (like Dasein). In this context, we begin to understand that the depth of consciousness in the concept of early Heidegger can be associated with its temporality. In fact, towards the end of "Being and Time", Heidegger, thinking more and more about the understanding of time from the horizon of being, begins to form similar ideas about understanding itself, that is, about human consciousness, in the sense that consciousness itself arises from the horizon of time (and being). What, then, is pure human consciousness the pure time? Does not this mean that the original meaning of consciousness is in its directed temporalizing. This temporalizing of consciousness of human (as a thinking being), which arises from the future, is perceived in three modes and reveals the fundamental nature of the consciousness itself (thinking is a stream of consciousness and, in such a context, directed understanding). Paraphrasing Heidegger, we say that the ontological meaning of pure human consciousness is revealed as temporality. Already after writing Being and Time, Heidegger thinks about the origins of the European consciousness, its comprehending from the depths (originality) of the being of European culture. Conclusions. The early Heidegger seeks the purity of being and, at the same time, strives more and more to understand the essence of the purity of human thinking. All of Heidegger’s work is a consistent transition from human understanding of the purity of being (Dasein) to the purity of thinking of a human himself. In this sense, there is a transformation of M. Heidegger’s consciousness from fundamental ontology (Dasein) in the early period to existential anthropology (human consciousness) in the late period.